PENGARUH BOBOT TELUR TERHADAP DAYA TUNAS DAN DAYA TETAS TELUR ITIK - Tri Syamsiningsih; Doso Sarwanto; Sulistyaningtyas (MEDIA PETERNAKAN, 2023)
The research entitled The Effect of Egg Weight on Shoot and Hatchability of Duck Eggs aims to determine the effect of egg weight on budding and hatchability in duck egg hatching. The material used in the study was 30 duck eggs. The research method used a completely randomized design (CRD) with egg weight treatment (P1: duck egg weight 60-65 grams, P2: duck egg weight 66-70 grams and P3: duck egg weight more than 70 grams) repeated 10 times. The variables observed were shoot and hatchability of duck eggs. The results showed that egg weight had no significant effect (P>0.05) on shoot and hatchability of duck eggs. Keyword: Egg Weight, Shoot Viability, Hatchability, Duck Eggs.